Efficacy and safety of oral sodium bicarbonate in kidney-transplant recipients and non-transplant patients with chronic kidney disease: a systematic review and meta-analysis - Wu, Yun; Wang, Ying; Huang, Weijun; Guo, Xi; Hou, Baoluo; Tang, Jingyi; Wu, Yuqi; Zheng, Huijuan; Pan, Yanling; Liu, Wei Jing (Frontiers in Pharmacology, 2024)
Introduction We investigated the efficacy and safety of oral sodium bicarbonate in kidney-transplant recipients and non-transplant patients with chronic kidney disease (CKD), which are currently unclear. Methods PubMed, Cochrane Library, Embase, and Web of Science were searched for randomized controlled trials investigating the efficacy and safety of sodium bicarbonate versus placebo or standard treatment in kidney-transplant and non-transplant patients with CKD. Results Sixteen studies of kidney-transplant recipients (two studies, 280 patients) and non-transplant patients with CKD (14 studies, 1,380 patients) were included. With non-transplant patients, sodium bicarbonate slowed kidney-function declines (standardized mean difference [SMD]: 0.49, 95% confidence interval [CI]: 0.14–0.85, p = 0.006) within ≥12 months (SMD: 0.75 [95% CI: 0.12–1.38], p = 0.02), baseline-serum bicarbonate <22 mmol/L (SMD: 0.41 [95% CI: 0.19–0.64], p = 0.0004) and increased serum-bicarbonate levels (mean difference [MD]: 2.35 [95% CI: 1.40–3.30], p < 0.00001). In kidney-transplant recipients, sodium bicarbonate did not preserve graft function (SMD: -0.07 [95% CI: -0.30–0.16], p = 0.56) but increased blood pH levels (MD: 0.02 [95% CI: 0.00–0.04], p = 0.02). No significant adverse events occurred in the kidney-transplant or non-transplant patients (risk ratio [RR]: 0.89, [95% CI: 0.47–1.67], p = 0.72; and RR 1.30 [95% CI: 0.84–2.00], p = 0.24, respectively). However, oral sodium bicarbonate correlated with increased diastolic pressure and worsened hypertension and edema (MD: 2.21 [95% CI: 0.67–3.75], p = 0.005; RR: 1.44 [95% CI: 1.11–1.88], p = 0.007; and RR: 1.28 [95% CI: 1.00–1.63], p = 0.05, respectively). Discussion Oral sodium bicarbonate may slow kidney-function decline in non-transplant patients with CKD taking sodium bicarbonate supplementation for ≥12 months or a baseline serum bicarbonate level of <22 mmol/L, without preserving graft function in kidney-transplant recipients. Sodium bicarbonate may increase diastolic pressure, and elevate a higher incidence of worsening hypertension and edema. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/, identifier CRD42023413929.